A kinanthropometric profile and morphological prediction functions of elite international male javelin throwers - de Ridder, J. H.; Kruger, A.; Underhay, C.; Grobbelaar, H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Kinantropometric studies on elite athletes help in the understanding of the morphological, biomechanical and physiological demands of modern training methods and the optimal requirements for successful participation as well as determining the selection criteria for the identification of talented young athletes. The purpose of this study was to describe the body composition and somatotypes of elite international javelin throwers and identify the variables that discriminate best between elite javelin throwers and other sportsmen. The results of this study could help in identifying young talented athletes and also guide in training methods to help attain the required body composition for optimum performance in javelin throwing.